The Impact of Implementing Verbal Augmented Feedback on Lay-Up Exercises of Sports Education College Student - Ardiansyah, Bahtiar; Hidayatullah, Fajar; Handayani, Heni Yuli; Himawan, Agus (Journal of Sport and Exercise Science, 2024)
Purpose: This research aims to determine the impact of implementing verbal augmented feedback on lay-up exercises among college sports education students. Materials and Methods: This research uses experimental research with a quantitative approach. Experimental research involves manipulating one or more variables to influence the variable being measured. The research population is sports education students from the class of 2022 STKIP PGRI Bangkalan. This study's data analysis was conducted using SPSS version 22. Result: In the normality test using Kolmogorov-Smirnov, the significance is 0.078, which means it is more significant than 0.05, so it is stated that it is normally distributed. In the comparison of the descriptive statistics table, the mean pre-test and post-test post-test showed an increase in results, so the provision of treatment on the test instrument can be stated as excellent and acceptable. In the Hypothesis test using the Paired sample T-test, the results of the post-test and pre-test significance values of the right and left lay-ups were smaller than 0.05. So, it is stated that the 2 hypothesis variables above are included in the acceptable significance value. Conclusion: Providing verbal augmented feedback greatly influences students' understanding of theory and practice through communication interactions. In its implementation, implementing verbal augmented feedback requires sufficient time to determine the implementation schedule, facilities and infrastructure, as well as evaluating notes to determine each student's progress at each meeting. Verbal augmented feedback is an old method that coaches often use during training sessions, but they often need to be made aware of this. So, the method of implementing verbal augmented feedback can be explored further by lecturers, teachers, and trainers to provide an understanding of the material provided through communication interactions (feedback).